The environment in Petrobrás magazine (1961-1979): Meaning mobilized by corporate discourse - Oliveira, Lídia; Almeida, Janaína; Caria, Ana (Review of Business Management, 2023)
Purpose – This study analyzes the ideological constructions of Petrobras’ corporate environmental discourse during the period from 1961 to 1979. Theoretical framework – The paper uses Thompson’s (2011) critical conception of ideology, specifically its modes of operation and strategies of symbolic construction. Design/methodology/approach – The study develops a critical analysis through qualitative and documental research based on Petrobras, making use of Thompson’s (2011) depth hermeneutics approach. Findings – Petrobrás magazine was used as a communication and accountability tool through which symbolic forms were disseminated, in response to environmental pressures from society. Using a nationalist, developmentalist, and anthropocentric approach, these symbolic forms helped to hegemonize the understanding of reality, promoting the company and the regime. Practical & social implications of research – Through corporate and press discourse and strategies of symbolic construction, the research contributes to understanding the growing social awareness of the environment arising from organizational behavior. Originality/value – The study illustrates how corporate environmental discourse, far from being neutral, contributes to establishing and sustaining relations of domination. It also provides insights to understand how Petrobras kept reporting reality and the basis of today’s narrative. Keywords: Corporate discourse, ideology, Petrobras, environmental reporting.